PENGEMBANGAN PRODUK HASIL TANGKAPAN PADA KELOMPOK ISTRI NELAYAN DESA LUMPUR, GRESIK - Elita Fidya Nugrahani; Kuntum Khoiro Ummatin; Anindita Adikaputri (Program Studi D4-Manajemen Bisnis, Jurusan Teknik Bangunan Kapal, Politeknik Perkapalan Negeri Surabaya, 2023)
Lumpur Village, Gersik, is a coastal area that has a huge potential for marine products, and most of the population works as fishermen. Marine products are usually sold directly to middlemen, and only a small portion was processed. On the other hand, fishermen's wives could improve their economies by helping to process marine products and increase their value. Thus, the development of marine products needs to be carried out. The methods used to obtain suitable products are interviews, observation, market research, and financial feasibility analysis. Based on interviews and observations, Lumpur Village, Gresik has 25 kg/day of shrimp potential. Based on market research, the processed shrimp preferred by 32% of respondents are nuggets. The Shrimp nuggets business run by fishermen's wives will be using sales methods both direct and online. The financial feasibility analysis shows that the Net Present Value is positive, and the Payback Period is less than the project duration; hence, this business is feasible.